Possibility of Reproduction of Linum usitatissimum L. from Seeds with Low Germination and Viability In Vitro Conditions - Mishchenko, Serhii; Kryvosheeva, Larysa (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The development of a method for the reproduction of flax (Linum usitatissimum L.) from seeds of low germination and viability was the goal of our research. To prevent damage to the seed embryo and weak seedlings for sterilization of the seeds aqueous NaOCl solution at a reduced concentration (1.5 %) and a reduced exposure (10 minutes) was applied. The effect of a combination of various combinations of phytohormones and other biologically active substances on the germination of flax seed was established. Cultivation of seeds in the Murashige and Skoog medium with macro elements and microelements in the full dose which includes 2.5 mg/L glycine, 0.2 mg/L thiamine, 1.0 mg/L pyridoxine, 5.0 mg/L ascorbic acid, 0.2 mg/L kinetin (КIN), 0.2 mg/L gibberellic acid (GA3), 4.0 m/L succinic acid, 12.5 g/L sucrose and does not contain nicotinic acid increases the seeds germination to 10.0–25.0 %. In this case, the explants were cultivated for 2–3 days at a temperature of 19–21 °C and further at a temperature of 22–24 °C. The White medium which contains 0.1 mg/L of 1-naphthylacetic acid (NAA) and 12.5 g/L of sucrose was used for microclonal propagation of the generated shoots. The proposed method provides the obtaining of valuable flax seed breeding material from the seed of low germination and viability, a high coefficient of its reproduction, which accelerates the breeding process.